If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) = (2x + -3) Reorder the terms: (2 + x) = (2x + -3) Remove parenthesis around (2 + x) 2 + x = (2x + -3) Reorder the terms: 2 + x = (-3 + 2x) Remove parenthesis around (-3 + 2x) 2 + x = -3 + 2x Solving 2 + x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + x + -2x = -3 + 2x + -2x Combine like terms: x + -2x = -1x 2 + -1x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + -1x = -3 + 0 2 + -1x = -3 Add '-2' to each side of the equation. 2 + -2 + -1x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -3 + -2 -1x = -3 + -2 Combine like terms: -3 + -2 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 7x+11x=127+x | | 8-3c=2c-2 | | 6x-5=14x-77 | | 23x-24=22 | | 3x+24=11x-56 | | 18x^2+18x+4=0 | | 4x^2-14x+6=0 | | 8x-28=44 | | 5x+5=35 | | 3x^2-1200=0 | | 2x^2+8x=0 | | 7x+7=0 | | 5-x-(x+3)-(3-2x)= | | (12x-2)=(3x+5) | | (7x-4)=(5x+8) | | -5x+14=-1 | | (10x-12)=(4x+3)+(x+5) | | 18x^2+33x-216=0 | | (7x-13)=(2x+1)+(3x+2) | | 12x^2-47x-40=0 | | 22x-32=56 | | 2(x-1)-6=10(1-x)+6 | | y+0.1=-22.4 | | -5p+10+2p=-5 | | -1.5x^2-2.5x=0 | | -1.5x-2.5x=0 | | (2x+5)=(4x-35) | | x^2+48x+47=0 | | 6+3x+6x=-3+x+1+7x | | 8-2v-2=3-3v | | 7x-8-3x=24 | | 1+9=9+1 |